Molecular epidemiology of Bordetella pertussis in the Philippines in 2012–2014. (June 2015) - Galit, Salvacion Rosario L.; Otsuka, Nao; Furuse, Yuki; Almonia, Daryl Joy V.; Sombrero, Lydia T.; Capeding, Rosario Z.; Lupisan, Socorro P.; Saito, Mariko; Oshitani, Hitoshi; Hiramatsu, Yukihiro; Shibayama, Keigo; Kamachi, Kazunari; et al.
Highlights: Genotypes of Bordetella pertussis in the Philippines were determined using clinical specimens . B. pertussis MT34 strain was the predominant strain in the Philippines during 2012–2014. All B. pertussis strains carried the virulence-associated allelic genes, ptxP1 – ptxA1 – prn1 – fim3A . The B. pertussis population in the Philippines is markedly different from that in other countries. Summary: Objectives: The present study was designed to determine the genotypes of circulating Bordetella pertussis in the Philippines by direct molecular typing of clinical specimens. Methods: Nasopharyngeal swabs (NPSs) were collected from 50 children hospitalized with pertussis in three hospitals during 2012–2014. Multilocus variable-number tandem repeat analysis (MLVA) was performed on the DNA extracts from NPSs. B. pertussis virulence-associated allelic genes ( ptxA, prn, and fim3 ) and the pertussis toxin promoter, ptxP, were also investigated by DNA sequence-based typing. Results: Twenty-six DNA extracts yielded a complete MLVA profile, which were sorted into 10 MLVA types. MLVA type 34 (MT34), which is rare in Australia, Europe, Japan, and the USA, was the predominant strain (50%). Seven MTs (MT29, MT32, MT33, and MT283–286, total 42%) were single-locus variants of MT34, while two (MT141 and MT287, total 8%) were double-locus variants of MT34. All MTs had the combination of virulence-associated allelic genes, ptxP1 – ptxA1 – prn1 – fim3A . Conclusions: The B. pertussis population in the Philippines comprises genetically related strains. These strains are markedly different from those found in patients from other countries where acellular pertussis vaccines are used. The differences in vaccine types between these other countries and the Philippines, where the whole-cell vaccine is still used, may select for distinct populations of B. pertussis .